2016
DOI: 10.1159/000448684
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Language Intervention Programme for Preschool Children

Abstract: Objective: This paper investigates the effectiveness of the Language Intervention Programme for the treatment of 14 preschool-aged children with primary language impairment. Patients and Methods: We used a waiting list control design, in which half the sample (7 children) received immediate intervention with the Language Intervention Programme, whereas the remaining children received treatment after a 4-week delay. The intervention consisted of 8 individual biweekly sessions. Outcome measures of language abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…This result agrees with previous studies that found the positive effect of speech therapy in cases of language delay in children [23]. However, this effectiveness was debatable in other studies depending on target group, cause of delay, and child's age [24][25][26].…”
Section: Discussionsupporting
confidence: 91%
“…This result agrees with previous studies that found the positive effect of speech therapy in cases of language delay in children [23]. However, this effectiveness was debatable in other studies depending on target group, cause of delay, and child's age [24][25][26].…”
Section: Discussionsupporting
confidence: 91%
“…(e.g. Smith-Lock, Leitao, Lambert & Nickels, 2013;Lousada, Ramalho & Marques, 2016;Hegazi, Neumann & Rosenfeld, 2020). These findings provide strong evidence of the need for identification and intervention when addressing children's speech and language needs.…”
Section: Speech-language Interventionmentioning
confidence: 69%
“…These potential linguistic delays were not significantly related to problem behaviors (Table 8); this probably reflects yet undetermined environmental variables. Nevertheless, the results justify implementing routine language screening in all childhood clinic visits [8][9][10]. Language development predicts the child's intellect, while language difficulty correlates with learning problems [11].…”
Section: Discussionmentioning
confidence: 99%